Price discrimination bans on dominant firms - Jan Bouckaert; Hans Degryse; Theon van Dijk (Center for Economic Studies and ifo Institute (CESifo), 2008)
Competition authorities and regulatory agencies sometimes impose pricing restrictions on firms with substantial market power the dominant firms. We analyze the welfare effects of a ban on behaviour-based price discrimination in a two-period setting where the market displays a competitive and a sheltered segment. A ban on higher-prices-to-sheltered-consumers decreases prices in the sheltered segment, relaxes competition in the competitive segment, increases the rival's profits, and may harm the dominant firm's profits. We show that a ban on higher-prices-to-sheltered-consumers increases the dominant firm's share of the first-period market. A ban on lower-prices-to-rival's-customers decreases prices in the competitive segment, lowers the rival's profits, and augments the consumer surplus. In particular, while second-period competition is relaxed by a ban on lower-prices-to-rival's-customers , first-period competition is intensified substantially, which leads to lower prices on-average over the two periods. Our findings indicate that a dynamic two-period analysis may lead to conclusions opposite to those drawn from a static one-period analysis.
Keywords: D11; 330; dominant firms; price discrimination; competition policy; regulation; Preisdifferenzierung; Marktmacht; Preisaufsicht; Wohlfahrtseffekt; Wettbewerbstheorie